2011
DOI: 10.1099/mic.0.041996-0
|View full text |Cite
|
Sign up to set email alerts
|

Induction of cell death after localization to the host cell mitochondria by the Mycobacterium tuberculosis PE_PGRS33 protein

Abstract: PE_PGRS33 is the most studied member of the unique PE family of mycobacterial proteins. These proteins are composed of a PE domain (Pro–Glu motif), a linker region and a PGRS domain (polymorphic GC-rich-repetitive sequence). Previous studies have shown that PE_PGRS33 is surface-exposed, constitutively expressed during growth and infection, involved in creating antigenic diversity, and able to induce death in transfected or infected eukaryotic cells. In this study, we showed that PE_PGRS33 co-localizes to the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
57
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(61 citation statements)
references
References 48 publications
4
57
0
Order By: Relevance
“…In this study, we demonstrated that the Mtb toxin TNT damages mitochondria, a key event in the necrotic cell death of Mtb-infected macrophages (Chen et al, 2006; Duan et al, 2002; Jamwal et al, 2013). The observed mitochondrial damage is a consequence of the NAD + glycohydrolase activity of TNT and does not require a direct interaction of TNT with mitochondria, in contrast to other Mtb proteins associated with mitochondria (Cadieux et al, 2011; Sohn et al, 2011). The key observation linking NAD + depletion by TNT to necrotic cell death was that inhibition or lack of RIPK3 and/or MLKL protected Mtb-infected macrophages from TNT-induced cell death.…”
Section: Discussionmentioning
confidence: 85%
“…In this study, we demonstrated that the Mtb toxin TNT damages mitochondria, a key event in the necrotic cell death of Mtb-infected macrophages (Chen et al, 2006; Duan et al, 2002; Jamwal et al, 2013). The observed mitochondrial damage is a consequence of the NAD + glycohydrolase activity of TNT and does not require a direct interaction of TNT with mitochondria, in contrast to other Mtb proteins associated with mitochondria (Cadieux et al, 2011; Sohn et al, 2011). The key observation linking NAD + depletion by TNT to necrotic cell death was that inhibition or lack of RIPK3 and/or MLKL protected Mtb-infected macrophages from TNT-induced cell death.…”
Section: Discussionmentioning
confidence: 85%
“…The ESX-5 system is crucial for the secretion of the Mtb PE/PPE family of proteins (Abdallah et al 2006(Abdallah et al , 2009. Interestingly, the PE_PGRS33 protein is transported to host cell mitochondria and induces programmed necrosis when expressed ectopically in mammalian cells (Cadieux et al 2011). It remains to be determined what the function of this protein is in the context of live Mtb infection.…”
Section: Mtb Genes Involved In Host Cell Programmed Necrosis Inductionmentioning
confidence: 99%
“…The protein PE_PGRS33 (Rv1818c), for example, was described as exerting a cytotoxic effect on host cells (33,34). Interestingly, the gene encoding PE_PGRS33 in M. tuberculosis strains is not present in the genomes of Mycobacterium canettii strains, representing early branching tubercle bacilli with smooth colony morphology and showing lower virulence and persistence in animal infection models relative to M. tuberculosis (35).…”
Section: Mycobacterial Genomicsmentioning
confidence: 99%